Tax and Investment by Multinational Enterprises - Hanappi, Tibor (OECD Publishing, 2023)
This paper investigates two closely related questions concerning the responses of Multi-National Enterprise (MNE) investment to corporate income taxation using a panel of unconsolidated subsidiary-level and consolidated group-level data from the ORBIS database. First, the paper provides new evidence on the heterogeneity of investment responses to taxation across multinational firms. This paper finds that profit shifting opportunities, access to credit, and market power at the group level are associated with decreased investment sensitivity to taxation among MNE subsidiaries. Second, a new empirical approach is used to investigate how tax changes at the host jurisdiction level affect investment at the MNE group level and whether there are propagation effects to foreign subsidiaries within the same MNE group. This paper finds that taxation in one jurisdiction in which an MNE is active is positively associated with investment in its subsidiaries in other jurisdictions. This finding suggests that the well-document negative relationship between taxation and MNE investment within a host jurisdiction masks the MNE rebalancing the location of its investment to other host jurisdictions in response to changes in cross-jurisdictional tax rate differentials rather than purely decreasing its investment globally
Keywords: Finance and Investment; Taxation